A Brief Review on Perovskite Materials: Synthesis, Properties, and Applications - Debasmita Das (International Journal of Advance in Molecular Engineering, 2025)
Perovskite materials have emerged as a transformative class of compounds, capturing widespread interest due to their remarkable properties and diverse applications across various fields, including optoelectronics, catalysis, energy storage, and environmental technologies. The synthesis techniques, classification, and unique properties of perovskite materials are thoroughly examined in this paper, which highlights the materials' potential to completely transform a number of sectors. One of the standout features of perovskites is their highly tunable structure, represented by the general formula ABX₃, which allows for the customization of their optical, electronic, and chemical properties. This adaptability has positioned them as strong candidates for high-performance solar cells, with rapid advancements pushing power conversion efficiencies to unprecedented levels. Similarly, their excellent charge transport properties and solution-processable nature have made perovskites integral to next-generation light-emitting diodes (LEDs) and other optoelectronic devices, offering significant advantages in terms of efficiency, cost-effectiveness, and versatility. Beyond optoelectronics, perovskites demonstrate immense promise in catalysis, energy storage, and environmental remediation, owing to their high ionic conductivity, catalytic activity, and structural stability. However, challenges such as long-term stability, sensitivity to environmental factors, and the use of toxic elements like lead must be addressed to ensure their sustainable integration into practical applications. This review underscores the critical role of ongoing research in overcoming these barriers and unlocking the full potential of perovskite materials. By advancing stability, scalability, and environmental safety, perovskite technologies could drive significant progress in energy and environmental sectors, paving the way for innovative, sustainable solutions.
Keywords: Perovskite Materials; Renewable energy; optoelectronics; stability challenges; synthesis methods